Long‐term changes in structure and function of a tropical headwater stream following a disease‐driven amphibian decline. (29th December 2014) - Rantala, Heidi M.; Nelson, Amanda M.; Fulgoni, Jessica N.; Whiles, Matt R.; Hall, Robert O.; Dodds, Walter K.; Verburg, Piet; Huryn, Alex D.; Pringle, Catherine M.; Kilham, Susan S.; Lips, Karen R.; Colon‐Gaud, Checo; et al.
Summary Taxonomic and functional diversity in freshwater habitats is rapidly declining, but we know little about how such declines will ultimately affect ecosystems. Neotropical streams are currently experiencing massive losses of amphibians, with many losses linked to the chytrid fungus, Batrachochytrium dendrobatidis (Bd). We examined the ecological consequences of the disease‐driven loss of amphibians from a Panamanian stream. We quantified basal resources, macroinvertebrates, N uptake and fluxes through food‐web components and ecosystem metabolism in 2012 and 2014 and compared them to pre‐decline (2006) and 2 year post‐decline (2008) values from a prior study. Epilithon biomass accrued after the decline, more than doubling between 2006 and 2012, but then decreased fivefold from 2012 to 2014. In contrast, suspended particulate organic matter (SPOM) concentrations declined continuously after the amphibian decline through 2014. Biomass of filter‐feeding, grazing and shredding macroinvertebrates decreased from 2006 to 2014, while collector–gatherers increased during the same time period. Macroinvertebrate taxa richness decreased from 2006 (52 taxa) to 2012 (30 taxa), with a subsequent increase to 51 taxa in 2014. Community respiration, which initially decreased after the amphibian decline, remained lower than pre‐decline in 2012 but was greater than pre‐decline values in 2014. Gross primary production remained low and similar among years, while <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3r5mhjbv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NH4+</alternatives> uptake length in both 2012 and 2014 was longer than pre‐decline. Nitrogen flux to epilithon increased after the decline and continued to do so through 2014, but N fluxes to fine particulate organic matter and SPOM decreased and remained low. Our findings underscore the importance of studying the ecological consequences of declining biodiversity in natural systems over relatively long time periods. There was no evidence of functional redundancy or compensation by other taxa after the loss of amphibians, even after 8 years.